MOLECULAR CHARACTERIZATION OF DENGUE VIRUS AND VECTORIAL COMPETENCE OF AEDES MOSQUITOES: A LOCAL MODEL OF XENOMONITORING (FUDMA JOURNAL OF SCIENCES, 2023)
Dengue is a major public health concern throughout tropical and sub-tropical regions of the world. Dengue virus is transmitted by infected female mosquitoes mainly of the species of Aedes aegypti and Ae. albopictus.Vector of Aedes mosquito populations may present different levels of competence for arbovirus transmission.Therefore, this study aimed at detecting DENV serotypes circulating and vectorial competence of adult field collected Aedes populations from selected local government areas of Kaduna State, Nigeria. A total of 233 mosquitoes were collected, identified morphologically to species level using coloured identification keys of Rueda and dissected under a dissecting microscope each species identified was tested in a pools of 20 individuals. Their bodies and head/salivary glands were separated and transferred to separate microtubes. RNA extraction was done using viral RNA extraction kit and semi-nested reverse transcription-polymerase chain reaction (RT-PCR) was used to amplified for DENV serotypes in the head/salivary glands of the Aedes mosquitoes. The study morphologically identified Ae. aegypti, Ae. vittatus and Ae. Furcifer. Aedes aegypti is the most abundant species 77.3%(180/233)  while Ae. furcifer 10.3% (24/233) were the least. DENV serotypes were detected in 76.9%(10/13) of the pools of Aedes mosquitoes in the study areas. DENV1-3 serotypes were detected in Ae. Aegypti, DENV2 was detected in Ae. vittatus and DENV 2 and 3 were detected in Ae. Furcifer. Dengue virus 2 was the most detected serotypes in the study areas. PCR pools screening infectivity prevalence were found to be 7.07% (95% CI- 3.38-11.77). Thus, the finding...
Keywords: Molecular characterization; Dengue Virus; Serotype; Xenomonitoring; Vectorial competence